The Effect of Reputation, Responsiveness, Giving Gifts and Recommendations on Customers Moving to Branch BNI Syariah Meulaboh Branch - Fahmi, Ijal; Rizal, Syamsul; Hamdani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
The aim of this research is to measure the effect of reputation, responsiveness, gift-giving, and recommendation to customer bank switching behavior in the Bank BNI Meulaboh. Independent variables including are reputation, responsiveness, gift-giving, and recommendation. Multiple Regression Analysis methods are chosen by using Liker Scale with 100 samples. The result of this research shows for simultan test that dependent variable brand switching (Y) can be effected by independent variable reputation (XI), responsive (X2), gift-giving (X3) and the last recommendation (X4) with a significant 0, 000 < 0, 05. The result of this research shows for partial test that dependent variable brand switching (Y) can be effected by independent variable reputation (XI) with a significant 0,010 < 0,05 , responsive (X2) with a significant 0,004 < 0,05, gift-giving (X3) with a significant 0,000 < 0,05 and the last recommendation (X4) with a significant 0, 020 < 0, 05.